The junior South African individual scale as predictor of scholastic achievement at Sub A, Sub B & Std One levels - Le Roux, D M (Department of Psychology, 2016)
This study examines the relationship between the eight subtest form of the Junior South African Individual Scale (JSAIS - 8) and scholastic performance at Sub A, Sub B and Std One levels, as measured by teacher evaluations. An unreferred sample of 104 pupils who had been tested on the JSAIS- 8 in their Sub A year were followed up at the end of Std One. The pupils' three sets of year-end symbols, as recorded in the official school records, were obtained. Pearson correlations were calculated between the Global, Verbal Performance and Numerical Scales and each of the subtests on the one hand, and selected school subjects and a computed average of the subjects on the other. The JSAIS scales and subtests were regressed on the computed averages for each standard. A test was performed to evaluate the longitudinal stability of the correlation matrix of Pearson correlations. The results were compared with those of similar studies employing non-South African intelligence scales, and with a study employing the full, twelve subtest version of the JSAIS (JSAIS - 12). The values of the correlations yielded were found to be of the same general magnitude as those reported in studies employing non-South African scales. The test for the longitudinal stability of the Pearson correlation matrix indicated that the test probably predicted equally over the three standard levels. The Global, Verbal and Numerical Scales and their associated subtests correlated moderately to highly with measures of scholastic achievement. The Performance Scale and its subtests yielded lower and sometimes non-significant correlations. Some discrepancies were noted between the results of the present study and that which employed the JSAIS - 12. It was observed that three of the five subtests which yielded the highest correlations with scholastic achievement in the study employing the JSAIS - 12 are excluded from the JSAIS - 8. The possibility of substituting these subtests for three subtests currently incorporated in the JSAIS - 8 was explored. Limitations of the present study were discussed and the tentative nature of the findings emphasised. Suggestions were made for further research.